The conceptual idea of recycling used cooking oil mobile application: A recommendation for environment sustainability / Mudiana Mokhsin ... [et al.] - Mokhsin, Mudiana; Harun, Afdallyna Fathiyah; Abu Bakar, Murshidan; Abdullah, Fariq; Japar, Ar Eirwan (Universiti Teknologi MARA, Sabah, 2020)
In general, most of the consumers in Malaysia would throw away their cooking oil just after one or two times of usage. Waste of the cooking oil is one of the root causes of water pollution as well as the cause of clogged the sink and drainage system in the residential areas. These situations occur due to bad habits of people to simply throw away used cooking oil that would affect and harm the environment. As the world moves forward to a sustainable city and greener environment, the society need to tackle this bad habit from becoming worse. This paper proposes a conceptual idea on how to educate, promote, create awareness as well as encourage the public to be more responsible in managing and disposing used cooking oil. The objective of this study is also aligned and inspired by the United Nations Sustainable Development Goals SDG 1: No Poverty and SDG 12: Responsible Consumption and Production.